An updated review of industrially relevant titanium dioxide and its environmental health effects - Ayorinde, Taiwo; Sayes, Christie M. (Journal of hazardous materials letters, 2023)
Titanium dioxide (TiO2) is a metal oxide that occurs naturally when titanium reacts with airborne oxygen. It has various attractive and beneficial properties, such as thermal stability, photocatalysis potential, and resistance to ultraviolet radiation. As a result, it is widely used in industrial processes and commercial products. The physicochemical properties of TiO2 can vary depending on the material's primary particle size, crystallinity, and formulation. Different properties have been found to cause different toxicological responses. While most studies have focused on the effects of exposure to nano-TiO2, little attention has been given to other relevant TiO2 materials. In this review, we examine the toxicological profile of both titanium dioxide nanoparticles and pigmentary TiO2. This review aims to provide reliable information on titanium dioxide toxicity for public and private stakeholders to use in risk assessments.